2002
DOI: 10.1080/01650250143000337
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for collaborative and individual everyday problem solving in later adulthood

Abstract: Individual and contextual predictors of preferences for solving everyday problems alone and in collaboration with others were investigated in a sample community-dwelling older adults (M age7 1.80 years, SDˆ5.78, rangeˆ56-87, 51 men, 56 women). Gender differences in problem-solving preferences were found in gender-stereotyped domains (e.g., meal-preparation; house repair). In several problem domains, more positive social comparisons of problem-solving ability were related to greater preferences for solving prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 34 publications
5
65
1
Order By: Relevance
“…Future research should focus on disaggregating aspects of the “dependent” profile. A first step would be to distinguish different functions of including others, such as information or advice seeking, compensating for one’s own perceived or actual deficits, or collaborating to make joint decisions (see Meegan & Berg, 2002; Strough et al, 2002). Additional research is necessary to investigate whether focusing on multidimensional profiles (as opposed to styles in isolation) distinguish negative and positive real-world decision outcomes (Bruine de Bruin et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should focus on disaggregating aspects of the “dependent” profile. A first step would be to distinguish different functions of including others, such as information or advice seeking, compensating for one’s own perceived or actual deficits, or collaborating to make joint decisions (see Meegan & Berg, 2002; Strough et al, 2002). Additional research is necessary to investigate whether focusing on multidimensional profiles (as opposed to styles in isolation) distinguish negative and positive real-world decision outcomes (Bruine de Bruin et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…One study showed a positive association between rational and dependent styles (Loo, 2000), suggesting that people with rational styles may deliberate with others. However, individuals may involve others in the decision-making process for different reasons (see Meegan & Berg, 2002; Strough, Cheng, & Swenson, 2002). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is empirical evidence showing that old women tend to solve everyday problems in female-stereotyped domains, such as meal preparation more often alone than men who prefer to complete such tasks in collaboration. This may further indicate the socialisation of gender-specific skills and responsibilities within this cohort (Strough et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To examine this aspect of dyadic cognition, metacognitive questionnaires have been used in several studies on decision-making as well as other domains of dyadic cognition (Strough, Cheng, & Swenson, 2002). For example, Berg et al (2003) found that couples report that when collaborating in everyday life, they often divide and delegate labour.…”
Section: Interdyadic Differences In Decision-making: Explanatory Concmentioning
confidence: 99%